Redistribution in collective pension arrangements without a sponsor guarantee: Hidden versus explicit risk transactions. (15th April 2022) - Yi, Lu; Sanders, Barbara; Bégin, Jean-François
Abstract: In collective pension arrangements without a sponsor guarantee, assets and liabilities are commingled, and members' benefits are adjusted to reflect emerging plan experience. Stakeholders pay attention to the fairness of the intergenerational transactions arising from the inclusion of certain design elements; however, implicit intergenerational transactions exist even in pure collective defined contribution (CDC) arrangements without any such explicit stabilization mechanisms. In this study, we find that the implicit risk transactions are uneven: significant value transfers among cohorts can result from joining a pure CDC plan. We then compare these to the additional value transfers arising from explicit stabilization mechanisms.